The dialectic of the self and the Other between psychological preoccupation and novelistic writing – *The Foreigner* by Alia Mamdouh as a model - boudiaf, ahmedaminef (El Omda in Linguistics and Discourse Analysis, 2025)
The novel is considered the most appropriate space in which arise a set of confrontations and conflicts that manifest themselves in different forms. From then on, these research dissertations came to be situated at some of the manifestations of this dialectic in the contemporary Arab novel, and we have not found a better one than the writings of the Iraqi novelist Alia Mamdouh to highlight at through them the various manifestations of these